Perceived Social Support and Glycemic Control among Type 2 Diabetes Patients in a Tertiary Care Center in Chennai, Tamil Nadu, India - Deepanchakravarthi V; S. Arun Murugan; Shruthee SG (Indian Association of Preventive and Social Medicine, 2024)
Introduction: Support from the external environment for enabling behavioral change, is often instrumental in mediating glycemic control in patients coping with diabetes. While evidence is scant in the Indian setting, there is a lack of consistency in findings among studies done elsewhere. Objective: To assess the perceived availability of social support and its association with glycemic control among type 2 diabetics. Method: Between October and December 2019, Cross sectional study was conducted among 150 adult patients, selected using convenient sampling method at the Diabetology clinic in a tertiary care centre in Chennai. Outpatients with a confirmed diagnosis of type 2 diabetes for at least one year, were recruited by convenient sampling. Perceived social support was assessed using the RAND-MOS social support survey instrument, while average of last three fasting blood glucose (FBG) readings determined glycemic status. Non-parametric Kruskal Wallis and Mann-Whitney U tests were used to analyze association of social support with glycemic control and socio-demographic determinants. Spearman's correlation coefficients with 95% CIs are reported for association of individual domain scores with average FBG. All analyses were performed with SPSS Version 23. Results: Study participants were aged 35 to 85 years, and living with type 2 diabetes for a mean duration of 10 ± 7.7 years. The average FBG in the past year ranged from 79 to 398 mg/dl in these patients, with 41 (27%) and 109 (73%) being classified as having good and poor glycemic control, respectively. The median (IQR) social support summary score was 62 (40-81) on a scale of 0 - 100; perceived social support was reportedly low, intermediate, and high in 36 (24%), 74 (49%) and 40 (27%) participants, respectively. The level of social support was not found to be significantly associated with glycemic control (P=0.628); average FBG and summary social support score showed no correlation [ρ=.081 (95% CI: -.097, .253), P =.322]. Conclusion: While a three- fourths majority reported availability of social support for coping with diabetes, this was not found to be significantly associated with glycemic status. The potential role of support networks, beyond the immediate family, in improving health outcomes needs to be examined.